Water-Response Materials in the Medical Field - Lin, Jiahao (Transactions on Environment, Energy and Earth Sciences, 2026)
Water-response materials (WRMs) are intelligent materials that shift shape, swell, or disintegrate with water. Biocompatibility facilitates use in medicine. At present, in biomedical fields such as bone defect repair and artificial muscle, traditional materials still face significant challenges in terms of biocompatibility, functional adaptability and minimally invasive implantation. The paper is a summary of WRMs' principles, categories, and preparation procedures, with an emphasis on the treatment of bone defects and the artificial muscle. The problems involving response stability, functions, and the limitations of scalability are discussed. The direction for the future is a move toward precision, multi-response synergy, and merging with 4D printing. WRMs are capable of breaking through the limitations of ordinary alloys, increasing biological compatibility, and decreasing the necessity for follow-up surgery, and consequently promoting the further development of minimally invasive medicine. This study systematically reviews the design principles and application frontiers of water-responsive materials, providing crucial theoretical basis and material selection for the development of the next generation of intelligent medical devices.
Keywords: Water-responsive materials; Biomedical use; Hydrogel; 4D printing; Repair.